Specialists’ Dual Practice within Public Hospital Setting : Evidence from Malaysia - Malindawati, Mohd Fadzil; Sharifa Ezat, Wan Puteh; Azimatun, Noor Aizuddin; Zafar, Ahmed (MDPI, 2022)
In line with the commitment of the Malaysian government and Ministry of Health to prevent the brain drain of specialists from public hospitals, they have been permitted to perform dual practice within the public hospital setting (DPH) since 2007. DPH allowed them to hold jobs in both public and private practices within the same public hospitals that they are affiliated to, permitting these specialists to treat public and private patients. Nevertheless, the information regarding DPH in Southeast Asia region is still limited. This narrative review provides insight into the implementation of DPH in Malaysia. It highlights that DPH has been well-governed and regulated by the MOH while serving as a means to retain specialists in the public healthcare system by providing them with opportunities to obtain additional income. Such a policy has also reduced the financial burden of the government in subsidizing healthcare. However, as in other countries with similar policies, multiple challenges have arisen from the implementation of DPH in Malaysia despite its positive achievements and potentials. This paper concludes that proactive governance, monitoring, and regulation are key to ensure the success of DPH